The Influence of Economic Fundamentals on The Company’s Financial Performance, Implications for Stock Returns in The Oil and Gas Mining Sub-Sector Located on The Indonesia Stock Exchange (BEI) In 2016-2021 - M Aldi Zikri aldi; Rum Hendarmin; Aris Munandar (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine how the influence of financial performance on the company's implications on stock returns. This study uses 9 companies that have been listed on the Index Stock Exchange (IDX) from 2016 to 2021 for 5 years. The statistical method used in this study is Eviews 10. The results show that the economic fundamentals are seen from interest rates, ROA, and ROE, on stock returns. Determination of the sample in this study using a purposive sampling method. Based on the analysis of the results of the research, the Economic Fundamental Variable (X) has a significant effect on stock returns. Variable Return on Equity (Z1) has no significant effect on stock returns. The stock return variable (Z2) has a significant effect on stock returns. The coefficient of determination from the results of the research is that the Adjusted R Square (R2) number is 0.310850 or 31.08%. The results of this statistical calculation mean that the ability of the independent variable to explain the variation in the change in the dependent variable is 31.08%, while the remaining 68.92% (100% - 31.08%) is influenced by other factors outside the research variables.